THE NEXUS BETWEEN CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE IN NIGERIAN FIRMS: THE ROLE OF INTELLECTUAL CAPITAL AS A MODERATOR - Ogbeide, S. O; Obaretin, O. (Journal of Allied Research in Management and Entrepreneurship (JARME), 2022)
The association between corporate governance and financial performance has been a subject of debate in the academic circle. While scholars suggest that corporate governance mechanisms impact financial performance, the relationship between the two remains inconclusive, complex, and mix. This paper seeks to examine the association between corporate governance and financial performance, considering the global context of corporate giant failures in the late 1990s and early 2000s. Scholarly works have established that poor corporate governance practices lead to corporate failure, promoting insider dealing. The paper explores the concept and essence of corporate governance, its mechanisms, processes, structures, and its role in directing and controlling corporate entities, including private sectors, public sectors, and financial institutions to achieve long-term strategic goals, take care of employees and local communities, and maintain harmonious relations with stakeholders. It is recognized that corporate governance aims to maximize shareholders’ wealth, maintain compliance with legal frameworks, reduce agency problems, increase corporate performance, and minimize negative externalities. The paper also examines the significance of financial performance and how it measures an entity’s income, returns, and increase in corporate value. The paper concludes that intellectual capital is vital information for investors to decrease indecision about the future prospects of the firm, stressing the need to disclose corporate governance principles and the connection of intellectual capital with corporate governance to realize performance.